2020
DOI: 10.14412/2074-2711-2020-5-60-65
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain in rheumatoid arthritis

Abstract: Objective: to identify the signs of neuropathic pain (NP) in patients with rheumatoid arthritis (RA) on the basis of the PainDETECT questionnaire and neurological examination.Patients and methods. A total of 208 RA patients (39 men and 169 women; mean age, 47.7 years) with chronic pain syndrome were examined. The patients underwent rheumatological and neurological examinations; NP was diagnosed using the PainDETECT questionnaire; inflammation severity (DAS28 index), pain intensity (VAS), affective disorders (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…As expected, it was also observed association of neuropathic pain with peripheral neuropathy ( P = 0.016) and neuropathy was found in 72.2% of patients with neuropathic pain as well as in the study of Filatova and Erdes [ 33 ] who found it in 96%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As expected, it was also observed association of neuropathic pain with peripheral neuropathy ( P = 0.016) and neuropathy was found in 72.2% of patients with neuropathic pain as well as in the study of Filatova and Erdes [ 33 ] who found it in 96%.…”
Section: Discussionsupporting
confidence: 81%
“…Age in this study, showed a surprisingly negative correlation with the number of falls in the previous 12 months (r = − 0.375, P = 0.032) different from that found in the general population in which age is an important risk factor [ 7 , 34 ]. Studies in RA found no relationship between age and falls [ 4 , 33 , 35 ]. We found a small negative association between age and falls, but the lower mobility of the older patients could be associated to a lower occurrence of falls.…”
Section: Discussionmentioning
confidence: 99%